Effectiveness of Using Digital Technologies in Mathematics Lessons within STEM Education (Journal of Educational Sciences, 2026)
This study examines the effectiveness of integrating the STEM approach with digital technologies in mathematics lessons. The experiment was conducted among 10th-grade students of general education schools in Almaty. In the experimental group, classes were organized using digital tools such as PhET Simulation, GeoGebra, Desmos, and Excel, while the control group was taught using traditional methods. During the study, students were offered interdisciplinary tasks: investigating the motion of a body thrown upward at an angle and graphically modeling motion equations. The results of theoretical modeling, practical simulations, and graphical analysis showed complete consistency, confirming the effectiveness of the STEM approach.The collected data were analyzed using both quantitative and qualitative methods. Findings demonstrated that the integration of the STEM approach with digital technologies increased students’ academic achievement by an average of 15–16% (p < 0.05). Furthermore, students’ research skills, modeling and data analysis abilities, as well as communication competences significantly improved. The study results confirm that, compared to traditional teaching, the STEM approach is more effective in improving educational quality, enhancing students’ interest in the subject, and developing their digital competencies.Keywords: STEM education,  mathematics teaching, digital technology, virtual laboratory, graphical modeling, research skills.